ANALISIS TINDAK TUTUR ILOKUSI EKSPRESIF DALAM DIALOG FILM ALI & RATU RATU QUEENS SUTRADARA LUCKY KUSWANDI SERTA IMPLEMENTASINYA PADA BAHAN AJAR TEKS DRAMA KELAS XI SMA - Elsa Putri Prisilla; Any Budiarty; Adi Rustandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Movies can be used as an effective way to convey messages and make them worthy of further review in speech act studies. This study aims to describe the form of speech and the function of expressive illocutionary speech acts in the dialogue of the film Ali & Ratu Ratu Queens directed by Lucky Kuswandi and their implications for teaching materials for drama texts in class XI SMA. This research use desciptive qualitative approach. The data source for this research is the dialogue film Ali & Ratu Ratu Queens directed by Lucky Kuswandi. The data collection technique used in this study is the speaking technique of free engagement. The results of the study show that there are 50 expressive illocutionary speech acts found in the Ali & Ratu Ratu Queens film directed by Lucky Kuswandi as many as 50 forms of speech in which 12 data show the function of rejecting, 10 data of the function of blaming, 9 data of the function of thanking, 8 data of the function of praising , 6 function data apologize, 2 function data congratulate, 2 data function receive, 1 data function pleasure, and 0 data or no greeting function. The results of this study were implemented in drama text teaching materials for class XI SMA KD 3.19 to analyze the content and language of the drama that was read or watched.